2007
DOI: 10.2332/allergolint.o-06-458
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Atopic Dermatitis Model Induced by Topical Application with Dermatophagoides Farinae Extract in NC/Nga Mice

Abstract: These results suggest that the model we have established is useful for not only elucidating the pathogenesis of atopic dermatitis but also for evaluating therapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
178
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(191 citation statements)
references
References 21 publications
12
178
0
1
Order By: Relevance
“…HDM was assumed to act not only as an allergen but also as a nonspecific irritant in AD skin lesions via a proteolytic activity of the HDM allergens. [25][26][27] In conclusion, this pilot study revealed that 24% of a group of allergic children from Cairo were sensitized to one or more of five strains of HDM, D. pteronyssinus and D. farinae being the most common. Testing children with several mite species would give information on the varied geographic distribution and might help efforts to develop more targeted specific immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…HDM was assumed to act not only as an allergen but also as a nonspecific irritant in AD skin lesions via a proteolytic activity of the HDM allergens. [25][26][27] In conclusion, this pilot study revealed that 24% of a group of allergic children from Cairo were sensitized to one or more of five strains of HDM, D. pteronyssinus and D. farinae being the most common. Testing children with several mite species would give information on the varied geographic distribution and might help efforts to develop more targeted specific immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…NC/Nga mice were challenged with Dfb ointment containing mite extract on the dorsal lesion; 2 wk later, these mice gradually began to develop symptoms of AD, including dryness, edema, and hemorrhage (28). Because P6 alone was difficult to dissolve in PBS at high concentrations, we developed P6-nano.…”
Section: P6-nano Treatment Ameliorates Admentioning
confidence: 99%
“…NC/Nga mice는 태어난 후 일반사육환경 (conventional system)에서 노출되면 사람의 아 토피피부염과 유사한 병변의 형태 즉, 딱지가 앉은 상처 및 작은 결정의 병변이 관찰되는 동물로서 아토피피부염 실험 동물로 사용되고 있다 [17]. Mite extract (Biostir mite extract antigen cream, BMAC)은 Dermatophagoides farinae crude extract (mite extract antigen, lyophilized)를 진드기 항원으로 제조된 것으로 진드기 항원 tween 20이 0.5% 함유된 ointment base로 제작된 것을 사용하였다 (Biostir, Hiroshima, Japan) [18]. IgE, IgG1 ELISA kit는 SHIBAYAGI사 (Shibukawa, Japan)제품, γ-PGA는 바이웰㈜에서 구입하였으며 평균 분자 량은 300 kDa이다.…”
Section: Methodsunclassified